2009
DOI: 10.1080/08958370802596892
|View full text |Cite
|
Sign up to set email alerts
|

Two-day inhalation toxicity study of methyl iodide in the rat

Abstract: The effects of inhaled methyl iodide (MeI) on clinical pathology parameters, glutathione (GSH) tissue levels, serum thyroid hormone and inorganic iodide concentrations, S-methylcysteine hemoglobin concentrations, and liver UDP-glucuronyltransferase activity were studied in the rat. Male rats were exposed by whole-body inhalation to 0, 25, or 100 ppm MeI, 6 h/day for up to 2 days. Serum cholesterol concentrations (both high-density lipoprotein [HDL] and low-density lipoprotein [LDL] fractions) were increased an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These studies are summarized briefly below, and presented in full as stand-alone papers in this issue. An in vivo 2-day inhalation mechanistic toxicity study-rats (Himmelstein et al, 2009). The objective of this study was to evaluate the toxicokinetic behavior of iodomethane in rats exposed by inhalation.…”
Section: Studies To Support Pbpk Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies are summarized briefly below, and presented in full as stand-alone papers in this issue. An in vivo 2-day inhalation mechanistic toxicity study-rats (Himmelstein et al, 2009). The objective of this study was to evaluate the toxicokinetic behavior of iodomethane in rats exposed by inhalation.…”
Section: Studies To Support Pbpk Modelsmentioning
confidence: 99%
“…The hormone changes observed in short-term and chronic rat exposure studies, and the alterations in thyroid weight and histology following chronic exposure, provide unequivocal evidence that iodomethane influences thyroid-pituitary function. The action of iodomethane on the rat thyroid was identified as an effect due to iodide, based (at least in part) on data from the 2-day exposure study in male rats and an understanding of the effects of iodide on thyroid function (Table 7) (Himmelstein et al, 2009). Exposure to iodomethane increases the serum iodide level, and this increase in iodide is known to have a direct action on thyroid function.…”
Section: Thyroid Tumor Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…In several of these studies, nasal irritation and thyroid effects have been observed in rats and late-term (gestation day [gd] 23–26) resorptions and thyroid effects have been observed in rabbits depending upon the exposure concentration, the duration and/or timing of exposure (Chamberlain et al, 1998; Kirkpatrick, 2002; Himmelstein et al, 2009; Nemec et al, 2009; Sloter et al, 2009). Extrapolations of the portal of entry (nose) and systemic dosimetry of MeI and its metabolite, iodide, can be accomplished using the anatomical and physiological framework from previous hybrid CFD/PBPK models developed for rats and humans.…”
mentioning
confidence: 99%